2016
DOI: 10.5966/sctm.2016-0177
|View full text |Cite
|
Sign up to set email alerts
|

Neural Progenitor-Like Cells Induced from Human Gingiva-Derived Mesenchymal Stem Cells Regulate Myelination of Schwann Cells in Rat Sciatic Nerve Regeneration

Abstract: Regeneration of peripheral nerve injury remains a major clinical challenge. Recently, mesenchymal stem cells (MSCs) have been considered as potential candidates for peripheral nerve regeneration; however, the underlying mechanisms remain elusive. Here, we show that human gingiva‐derived MSCs (GMSCs) could be directly induced into multipotent NPCs (iNPCs) under minimally manipulated conditions without the introduction of exogenous genes. Using a crush‐injury model of rat sciatic nerve, we demonstrate that GMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 59 publications
2
50
0
Order By: Relevance
“…41 A cell/EV-scaffold combined product was developed using either GMSCs (5 • 10 5 cells in 20 mL PBS) or GMSC-derived EVs (40 mg in 20 mL PBS) mixed with Gelfoam (4 • 4 • 3 mm). 30 The cell/EVscaffold product was transplanted and wrapped around the injury site of the sciatic nerve immediately after nerve crush injury. Mice with sciatic nerve injury and treated with Gelfoam only served as controls.…”
Section: Cell Migration Testmentioning
confidence: 99%
See 2 more Smart Citations
“…41 A cell/EV-scaffold combined product was developed using either GMSCs (5 • 10 5 cells in 20 mL PBS) or GMSC-derived EVs (40 mg in 20 mL PBS) mixed with Gelfoam (4 • 4 • 3 mm). 30 The cell/EVscaffold product was transplanted and wrapped around the injury site of the sciatic nerve immediately after nerve crush injury. Mice with sciatic nerve injury and treated with Gelfoam only served as controls.…”
Section: Cell Migration Testmentioning
confidence: 99%
“…In our previous study, we observed that transplanted GMSCs delivered in Gelfoam wrapped at the crush-injury site of the peripheral rat sciatic nerve did not cross the epineurium into the neural fiber compartment and appeared to exert their neurogenic effect via a paracrine mechanism. 30 In this study, we further explore the effect of GMSC-derived EVs in the repair/regeneration of PNI as an alternative therapeutic approach. Both immunofluorescence studies showed a significant decrease in b-tubulin III expression, a neuronal marker (Fig.…”
Section: Gmsc-derived Evs Promote Axonal Repair/ Regeneration Of Crusmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a variety of kinds of cells have been used for the neural repair. 2,[5][6][7][8] However, single-cell transplantation strategy cannot achieve a satisfying repair effect. In recent studies, combined strategy is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Once the sciatic nerve get injury, the motor function of leg would be affected. Gingiva-derived MSCs (GMSCs) have been shown to promote peripheral nerve repair as well by inducing remyelination by regulating the expression of the antagonistic myelination regulators, c-Jun and krox-20/ERG2 90. Studies showed that DPSCs could differentiate into Schwann cells in vitro.…”
mentioning
confidence: 99%